Gamification as a learning tool - Lopes, Rui Pedro (2017)
Higher Education Institutions have the missions of education, at a high level, research and coop- eration. Regarding education, HEI must create an appropriate environment for learning, towards high-level academic performance. Students must be motivated to use the learning strategies in and out of the classes, to be able to make the best result of the learning effort. People is motivated according to several factors, such as external in nature (earn more money, gain social status, have a higher grade, ...) or internal (intrinsic), which results from the core self. The latter is associated to the satisfaction people feel when doing something appealing. This paper describes the approach to applying gamification to a higher education subject in the course of computer science. It uses several game design mechanisms, such as adaptive challenges, rewards, curiosity and chance to increase the time students spend working, experiencing and learn- ing in a HEI. The sections in the curriculum are transformed into levels, awarding stars for increasingly com- plex achievements. There is also the concept of soft currency, which is used to increase the student autonomy and incentive the work load. Some games are also used as learning experiences, allow- ing collective knowledge building in the preparation and also playing the games. Keywords: Higher Education; Intrinsic motivation; Educational Games; Gamification